Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid